Simultaneous Estimation of Production Functions and Capital Stocks for Developing Countries - Dadkhah, Kamran M.; Zahedi, Fatemeh (The Review of Economics and Statistics, 1986)
Kamran M. Dadkhah, Fatemeh Zahedi, Simultaneous Estimation of Production Functions and Capital Stocks for Developing Countries, The Review of Economics and Statistics, Vol. 68, No. 3 (Aug., 1986), pp. 443-451